Shaping personal God’s image and it’s influence on interrelation - Tokarski, Stanisław (Studia Psychologica: Theoria et praxis, 2007)
Experiences that we derive from our families, mainly real and ideal father’s image as well as mother’s image become a model on basis of which we build our personal God’s image. A person who dominates in the family has particular impact on the process of shaping God’s image in person’s mind. Often this person is a father; although it’s not obvious any more. Personal God’s image is also created by not religious people. Our personal God’s image not only has influence on our religiosity and its development but also affects interrelations especially among family and love ones. In the process of individual therapy or psychological treatment a drawing can be used to help clients to express themselves and gives them a chance of showing their feelings, conflicts and desires.